2015
DOI: 10.1016/j.toxrep.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metal oxide nanoparticle toxicity using embryonic zebrafish

Abstract: Engineered metal oxide nanoparticles (MO NPs) are finding increasing utility in the medical field as anticancer agents. Before validation of in vivo anticancer efficacy can occur, a better understanding of whole-animal toxicity is required. We compared the toxicity of seven widely used semiconductor MO NPs made from zinc oxide (ZnO), titanium dioxide, cerium dioxide and tin dioxide prepared in pure water and in synthetic seawater using a five-day embryonic zebrafish assay. We hypothesized that the toxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 64 publications
4
67
0
Order By: Relevance
“…7 and 8), which is the opposite of what we hypothesized would occur based on the in vitro data. However, the exposure concentrations used in the zebrafish xenograft assay were lower than the effective inhibitory concentrations in in vitro studies, 23,39,40 and we also identified that the ZnO NP agglomerated and underwent considerable dissolution (*47%-50%) when prepared in water (data previously published 28 ). Therefore, we cannot distinguish whether this increase in glioblastoma proliferation is due to a low-exposure NP effect, an ionic effect, or a combination of both.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325supporting
confidence: 67%
See 3 more Smart Citations
“…7 and 8), which is the opposite of what we hypothesized would occur based on the in vitro data. However, the exposure concentrations used in the zebrafish xenograft assay were lower than the effective inhibitory concentrations in in vitro studies, 23,39,40 and we also identified that the ZnO NP agglomerated and underwent considerable dissolution (*47%-50%) when prepared in water (data previously published 28 ). Therefore, we cannot distinguish whether this increase in glioblastoma proliferation is due to a low-exposure NP effect, an ionic effect, or a combination of both.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325supporting
confidence: 67%
“…ZnO NPs with a primary particle size of 8.37 nm were synthesized using forced hydrolysis as described previously in Wehmas et al 28 One gram of zinc acetate dehydrate and 99.5:0.5 mL diethylene glycol:nanopure water mix were heated to 160°C for 90 min followed by multiple ethanol rinses and separation using centrifugation for 20 min at 20,000 rpm after each rinse. Immediately before exposure, an aliquot of ZnO NP and ZnO bulk material control were suspended in 100% DMSO at a concentration of 10 mg/mL and water bath sonicated (Ultrasonik NDI; NEY, Inc., Bloomfield, CT) for 20 min at room temperature.…”
Section: Zinc Oxide Nanoparticlementioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the NPs studied for their toxicity in zebrafish are inorganic (Wehmas et al 2015;Zhao et al 2013). Little is known about biodegradable NPs, except for chitosan NPs (Wang et al 2016;Yuan et al 2016).…”
Section: Other Nanoparticlesmentioning
confidence: 99%